The use and potential abuse of psychoactive plants in southern Africa: an overview of evidence and future potential - Nyazema, Norman Zimunda; Chanyandura, Jonathan Tinotenda; Egan, Bronwyn (Frontiers in Pharmacology, 2024)
Background Most Bantu ethnic groups in southern Africa utilize indigenous herbal medicines, some of which have psychoactive properties. Traditional medical practitioners (TMPs) commonly use them not only for divinatory purposes but to treat and manage mental and other illnesses. Unfortunately, the research on their results, risks, and benefits do not align. Little is known about their potential abuse among TMPs and community members in southern Africa. Herbal medicines are complex because whole plants are sometimes used, unlike in other treatments which use only one active ingredient. However, if the key mechanisms of action of these ethnomedicinal plants can be identified through socio-pharmacological research, useful botanical agents can be developed. A review of socio-pharmacological studies to evaluate the consequences of exposure to ethnomedicinal plants with psychoactive properties was conducted with the aim of identifying harm reduction strategies and investigating how the plants could be developed into useful botanicals. Method The search methods involved retrieval of records from PubMed/MEDLINE, Embase, Web of Science, Dissertations and Theses Global, and OpenGrey. The English language and human subjects were used as filters. In addition, some information was obtained from TMPs and community members. Results The following psychoactive plants were found to be commonly used or abused: Boophone disticha, Cannabis sativa, Datura stramonium, Leonotis leonurus, Psilocybe cubensis, and Sceletium tortuosum. The commercialization of Cannabis, L. leonurus, S. tortuosum, and Aspalathus is growing fast. The abuse liability of B. disticha, D. stramonium, and P. cubensis appears not to be appreciated. Five countries were found to have TMP policies and three with TMP Councils. Conclusion TMPs in the region are aware of the CNS effects of the identified psychoactive plants which can be explored further to develop therapeutic agents. There is a need to work closely with TMPs to reduce harm from the abuse of these plants.